APLIKASI DARI N-SOFT SET PADA DATA DENGAN OBJEK BERKELOMPOK - Shodik, Fajar; Nazra, Admi; Yanita, Yanita (LPPM Universitas Bina Bangsa, 2024)
In this paper, an application of N-soft set on data with grouped objects will be presented using the construction concept in strait soft set theory to solve a problem in the decision-making process. For each parameter, a weight value will be determined, and from this data, a threshold will be set in such a way that a T-level soft set form is possible. This research is a descriptive qualitative study with a case study approach. An interesting result from this study is that an object with the lowest rank can have the highest rank in a certain group of objects